THE INTERSECTION OF TIME: THE IMAGINARY MEETING AMONG RONGGOWARSITO, MANGKUNEGORO IV AND RADEN SALEH - Subiyanto, Subiyanto; Rustopo, Rustopo; Kartika, Dharsono Sony (ISI Press Institut Seni Indonesia Surakarta, 2024)
The 19th century was a turbulent period for the island of Java, especially for its Javanese inhabitants, who had recently survived a devastating conflict known as the Java War. Prince Diponegoro became a symbol of Javanese resistance and a pivotal figure, signifying the inception of the high colonial era under the rule of Pax Nederlandica. Key historical figures like Raden Ngabehi Ronggowarsito, Mangkunegoro IV, and Raden Saleh Syarif Bustaman came of age in this epoch. The research project seeks to juxtapose the thoughts of these three key historical figures. A historical approach is used to analyze the available primary and secondary data and to constitute a metaphorical approach for reading art through the prism of these three exceptionally talented figures. The creative process of “The Intersection of Time” has been produced based on various considerations. Their interactions resulted in (1) heightened social awareness, which is evident in the way their thought processes responded to contemporary socio-economic, political, and cultural conditions during their respective lifetimes; (2) increased aesthetic awareness, allowing for creative responses to their environment and contemporary circumstances through their work; and (3) enhanced spiritual awareness, informing their individual and collective initiatives to protect Java’s circumstance. Drawing from a profound understanding of Javanese history, the history of the three selected individuals, and their artwork, the film “The Intersection of Time” will effectively encapsulate the distinct spirit and zeitgeist of the 19th century, setting it apart from conventional historical narratives.